Calculation and Visualization of Software Product Metrics - Meyer, Matthias; Niere, Jörg (Proc. of the 3rd International Fujaba Days 2005, Paderborn, Germany)
The paper presents a further step of the Fujaba Tool Suite RE to support coarse-grained analyses based on metrics and especially polymetric views. Polymetric views are graphical representations of certain metric combinations. Following an interactive reverse engineering approach, polymetric views can be created on demand. The reverse engineer is able to define new polymetric view descriptions and create new views afterwards.

Generation of Type Safe Association Implementations - Travkin, Dietrich; Meyer, Matthias (Proc. of the 3rd International Fujaba Days 2005, Paderborn, Germany)
Model driven development facilitates the specification of software models from which code can be generated automatically. In practice, a software system can often not be modelled completely. Developers still have to implement parts of it manually and thus have to work with the generated code. Therefore, the usability of the code is important. The Fujaba Tool Suite is a UML case tool which allows to model the structure and behaviour of a system with UML diagrams and to generate Java code for the specifications. However, the code currently generated for associations is not type safe. Furthermore, a lot of code is added to the implementation of the model classes which decreases their usability. In this paper, we present an approach to generate type safe association implementations in Java which also improves the readability and usability of the generated code.

On Approximating Real-World Halting Problems - Köhler, Sven; Schindelhauer, Christian; Ziegler, Martin (Fundamentals of Computation Theory)

An Explicit Solution to Post’s Problem over the Reals - Meer, Klaus; Ziegler, Martin (Fundamentals of Computation Theory)

Computability and Continuity on the Real Arithmetic Hierarchy and the Power of Type-2 Nondeterminism - Ziegler, Martin (Proc. CiE 2005: New Computational Paradigms)
The sometimes so-called Main Theorem of Recursive Analysis implies that any computable real function is necessarily continuous. We consider three relaxations of this common notion of real computability for the purpose of treating also discontinuous functions f:R->R: *) non-deterministic computation; *) relativized computation, specifically given access to oracles like 0' or 0''; *) encoding input x and/or output y=f(x) in weaker ways according to the Real Arithmetic Hierarchy. It turns out that, among these approaches, only the first one provides the required power.

Computational Power of Infinite Quantum Parallelism - Ziegler, Martin (International Journal of Theoretical Physics)

Methods to lead the user to significant processes in a 3D material flow simulation - Dangelmaier, Wilhelm; Mueck, Bengt; Fischer, Matthias; Mahajan, Kiran; Laroque, Christoph (Simulation in wider Europe - 19th European Conference on Modelling and Simulation ECMS 2005)

Channel-Adaptive Schedulers with State-of-the-Art Channel Predictors - Aguiar, A.; Wolisz, A.; Lederer, H.; Karl, Holger (Proceedings of the 11th European Wireless Conference 2005)

Glaschick, Rainer: Integrative Approach of Web Services and Universal Plug and Play within an AV Scenario - Loeser, Christoph; Drüke, Isabell; Oesterdiekhoff, Brigitte (IEEE International Conference on Industrial Informatics (INDIN))

Glaschick, Rainer; Service Oriented Interface Design for Embedded Devices - Oesterdiekhoff, Brigitte (IEEE International Conference on Emerging Technologies and Factory Automation (ETFA))